ARE GADGETS SAVIOURS IN SALVAGING SICK CASES – ULTRASOUND FOR BOTH NERVE BLOCKS AND VASCULAR ACCESS IN A CASE OF SEPTIC SHOCK - P, MADHULA; H, PRIYA; S, PARTHASARATHY (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Diabetes mellitus and diabetic foot syndrome presents to us with varying degrees of sepsis. We present a 52-year-old male with chronic diabetes with fore foot sepsis in shock. His blood sugar was controlled with insulin and the other parameters were normal. The blood pressure was around 90/50 mm Hg with noradrenaline support of 0.5 mic/kg/min. We secured a right internal jugular venous access with ultrasound (USG). The volume status as assessed by USG of the IVC was satisfactory. We administered popliteal sciatic nerve block along with saphenous nerve block visualizing the nerves with USG. The amputation of forefoot went on for 1 h where the hemodynamics remained stable at 100/70 mmHg. After the surgery was over, the patient was shifted to sick cubicle and in the next 6 h, the inotrope support was weaned off. The control of sugars was continuously monitored and kept under control. Any other form of neuraxial block could have been detrimental to him in the presence of hemodynamic imbalance. Such precise deposition of local anesthetics in the sciatic nerve is very difficult without the use of USG. We conclude that advanced gadgets may bring back hope in salvaging sick patients.